Long-term impact of the coach-athlete relationship on development, health, and wellbeing: stories from a figure skater. Issue 2 (3rd May 2020) - Kuhlin, Fanny; Barker-Ruchti, Natalie; Stewart, Carly
ABSTRACT: Coaches have been shown to detriment athletes' health, well-being and development. Knowledge of this long-term effect and what it means for athletes to live with such stories is under-explored. Using self-narrative, we examine the long-lasting impact of the coach-athlete relationship in the stories of a former figure skater, Fanny. Guided by Arthur Frank's dialogical analysis, we present creative non-fictional stories to show how Fanny made sense of her figure skating experiences, which were framed by a sport investment narrative and a career-wrecking injury that terminated her dream of becoming a professional figure skater. We suggest that if handled as an act of self-care, storytelling can re-configure the dominant coach-athlete relationship and sport investment narrative and help athletes to understand and reconstruct their stories. Finally, we reflect upon the impact of Fanny's story on her advisers and consider the pedagogical implications of such narrative work in sport coaching and sport education.